SecureTrustManagementinMulti-CloudEnvironment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Managing trust in cloud environment is the biggest obstacles in its adoption and increase in popularity among the clients. Since the cloud service users have to share all their confidential data with the cloud service providers, hence, it is obvious that they will choose service providers that are reliable. This article describes a solution for the problem of evaluating an unbiased subjective trust. We have described a method that divides the users chosen for feedback into two groups. These groups are interviewed by the trust service providers. These are the people who provide the trust worthiness and reliability of the cloud service providers. These trust ratings are provided basedon two things. First the feedback from different cloud service users. These users are divided into two groups. Firstly, the users who have used the service in their past. And second, the users who are currently using the services. Next measure is how well that cloud service provider adheres to the service level agreement.